2005
DOI: 10.1161/01.hyp.0000154786.17416.ea
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Genes Are Genetic Markers for Insulin Sensitivity and Resistance

Abstract: Abstract-Insulin resistance is a determinant of blood pressure variation and risk factor for hypertension. Because insulin resistance and blood pressure cosegregate in Mexican American families, we thus investigated the association between variations in 9 previously reported hypertension genes (ACE, AGT, AGTRI, ADDI, NPPA, ADDRB2, SCNN1A, GNB3, and NOS3) and insulin resistance. Families were ascertained via a coronary artery disease proband in the Mexican American Coronary Artery Disease Project. Individuals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…41 Anther study concluded that AGT may play a role in insulin resistance. 42 We have increased the homogeneity of study groups with MS by sub-grouping them according to clinical phenotype. This breakdown resulted in smaller sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…41 Anther study concluded that AGT may play a role in insulin resistance. 42 We have increased the homogeneity of study groups with MS by sub-grouping them according to clinical phenotype. This breakdown resulted in smaller sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Guo et al [36] reported that Mexican Americans with the T allele of AGT Met235Thr polymorphism had significantly higher insulin resistance and insulin sensitivity index. Although we did not use the glucose clamp method to evaluate insulin resistance, our results appear to be in accordance with this report and suggest that there may be a similar relationship between insulin resistance and AGT Met235Thr polymorphism in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies have revealed a number of potential mechanistic links between IR and elevated blood pressure: activation of renal sodium retention and the sympathetic nervous system by hyperinsulinemia, the usual concomitant of IR [8,9], resistance of blood vessels to the vasodilatory effects of insulin [10]. Additional data supported this concept of hypertension genes influencing IR [11].…”
Section: Discussionmentioning
confidence: 93%